El Dr. Paul Schaufelberger, un pionero de la geología del siglo XX de Costa Rica - Peraldo Huertas, Giovanni (2011)
We highlight the contributions of Dr. Paul Schaufelberger, who arrived to Costa Rica in 1929, contracted by the government, to teach geology at the Liceo de Costa Rica, Colegio Superior de Señoritas and Escuela Nacional de Agricultura. He was the director of the department of Geology and Mineralogy of the Centro Nacional de Agricultura located at San Pedro de Montes de Oca in what is now Ciudad Universitaria Rodrigo Facio. In his work Schaufelberger contributed scientific and disclosure papers about geology as known in his time. He wrote many papers that served as guidance for the lessons related to the subject of Geology in Costa Rica. He left the country in 1939 hired by the Fede- ración de Cafetaleros de Colombia with the purpose of performing geologic field studies intended for the betterment of the Colombian coffee industry. Schaufelberger died in 1976 in Colombia.